(untitled) (Journal of the College of Basic Education, 2026)
This research aims to identify the effect of the semantic mapping strategy on the achievement and intellectual motivation of students at the Institute for the Preparation of Technical Trainers in the subject of Basic Training Techniques, by verifying the following two hypotheses: There is no statistically significant difference at the significance level (0.05) between the average scores of the experimental group students who will study using the semantic map strategy and the average scores of the control group students who will study using the usual method in the achievement test. There is no statistically significant difference at the significance level (0.05) between the mean scores of the experimental group students who will study using the semantic map strategy and the mean scores of the control group students who will study using the usual method on the mental motivation scale. To verify the research objective and hypothesis, the researcher applied his experiment at the Institute for the Preparation of Technical Trainers to conduct the experiment there, during the second semester of the academic year (2024-2025), and the scientific content prescribed by the Middle Technical University/Basic Training Techniques course (theoretical lessons). After excluding a number of failing students, the number of students in the research sample became (54). The experimental group consisted of (29) students, and the control group consisted of (25) students. Equivalence was verified between the two research groups in the variables of chronological age in months, as well as in the intelligence test, and previous achievement (ministerial exam results). At the end of the semester, the two research groups were tested using the achievement test prepared by the researcher after verifying its validity and reliability, and finding its psychometric properties, and the mental motivation scale adopted by the researcher for (Al-Janabi, 2013). The results showed: Students in the experimental group who studied using the semantic mapping strategy outperformed students in the control group who studied using the traditional method on the achievement test and the mental motivation scale by a statistically significant difference In light of these findings, the researcher presented a number of recommendations and suggestions to further develop the research.